2005
DOI: 10.5860/crl.66.6.496
|View full text |Cite
|
Sign up to set email alerts
|

A Citation Study of the Characteristics of the Linguistics Literature

Abstract: By analyzing the citation patterns of the linguistics literature, the authors provide a bibliometric description of the discipline that will help librarians who have reference, instruction, or collection development responsibilities in this area understand it better. One important aspect of such an understanding is determining where linguistics classifies within the humanities, the social sciences, and the sciences. Based on several of the citation patterns discovered, namely the importance of recent publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Another study by Nkiko and Adetoro (2007) examined timeliness of cited sources and found out that more than 60% of citations were less than ten years old. Georgas and Cullars (2005), in their study, also found that the ages of citations were between one and fifteen years, and more than 5% of the citations were published between 1600 and 1960, which suggests that old materials were fairly cited.…”
Section: Citation Patterns and Scholarly Communication In Languagesmentioning
confidence: 91%
See 4 more Smart Citations
“…Another study by Nkiko and Adetoro (2007) examined timeliness of cited sources and found out that more than 60% of citations were less than ten years old. Georgas and Cullars (2005), in their study, also found that the ages of citations were between one and fifteen years, and more than 5% of the citations were published between 1600 and 1960, which suggests that old materials were fairly cited.…”
Section: Citation Patterns and Scholarly Communication In Languagesmentioning
confidence: 91%
“…This controversy about its classification may have contributed to a very scanty study on the citation patterns of the linguists and literary scholars as has been reported by Karisson (1994) and Georgas and Cullars (2005). Karisson contends that humanities in general have not been favoured by citation analysis, but linguistics is one of the lowest of the humanities disciplines.…”
Section: Citation Patterns and Scholarly Communication In Languagesmentioning
confidence: 99%
See 3 more Smart Citations